Mongolia Quarterly Economic Update, June 2012 - World Bank (Washington, DC, 2017)
The World Bank's Mongolia quarterly economic update assesses recent economic and social developments and policies in Mongolia. It also presents findings of ongoing World Bank activities in Mongolia. The Mongolian economy is continuing to grow at a very rapid pace, expanding by 16.7 percent year-on-year (yoy) in first quarter (Q1). This high growth however, is also fuelling inflation which touched 16 percent in April, well above the Bank of Mongolia's (BoM) inflation target of 10 percent. Increasing government spending on wages and salaries, large cash handouts to the general population, and burgeoning capital expenditures are adding to the demand pressures. Meanwhile, the worsening global economic outlook, in particular a faster than expected slowdown in China, Mongolia's largest trading partner, has negatively impacted export growth, resulting in deterioration in external balances. Under these circumstances, the advice to Mongolian policy-makers is to 'hold your horses' and adopt a more cautious macro-economic stance, tightening both monetary and fiscal policy to prevent further over-heating of the economy. The global economic outlook has deteriorated considerably in recent months. Financial conditions in high-income Europe, higher oil prices, and, most importantly, the slowing Chinese economy pose risks for Mongolia. The channels through which these operate include financial and trade linkages namely volatility in commodity prices and through demand from China for its mineral exports. Indeed, signs of these are already visible as demonstrated by the decline in exports in April. Other financial market linkages should also not be discounted: Mongolia's banking system, which has shown signs of overheating over the past year, is highly dollarized, with about a third of deposits denominated in dollars and easy convertibility out of the Mongolia Togrog. A sharp economic slowdown and/or an increased macroeconomic instability could expose the liquidity and asset quality vulnerabilities in individual banks and system overall.